Tobit and the »Torah for Exile« in Light of the Qumran Texts - Dimant, Devorah (Zeitschrift für Theologie und Kirche, 2022)
The recent decades have seen a surge of interest in the deuterocanonical books, namely, the Jewish works incorporated in the Christian Scriptures. Among them, the book of Tobit has garnered particular attention since recent findings shed new light on this work. Three such discoveries had a major impact on the study of Tobit.